Effectiveness of the neutralizing antibody sotrovimab among high-risk patients with mild-to-moderate SARS-CoV-2 in Qatar - Ahmed, Zaqout (2022)
ObjectivesTo estimate the real-world effectiveness of sotrovimab against severe, critical, or fatal COVID-19 in Qatar at a time in which most SARS-CoV-2 incidences occurred due to the BA.2 Omicron subvariant. MethodsWe conducted a matched case-control study among all individuals eligible for sotrovimab treatment per United States Food and Drug Administration guidelines in the resident population of Qatar. The odds of progression to severe forms of COVID-19 were compared in cases (treatment group) versus controls (eligible patients who opted not to receive the treatment). Subgroup analyses were conducted. ResultsA total of 3364 individuals were eligible for sotrovimab treatment during the study period, of whom 519 individuals received the treatment, whereas the remaining 2845 constituted the controls. The adjusted odds ratio of disease progression to severe, critical, or fatal COVID-19 comparing the treatment group to the control group was 2.67 (95% confidence interval 0.60-11.91). In the analysis including only the subgroup of patients at higher risk of severe forms of COVID-19, the adjusted odds ratio was 0.65 (95% confidence interval 0.17-2.48). ConclusionThere was no evidence for a protective effect of sotrovimab in reducing COVID-19 severity in a setting dominated by the BA.2 subvariant.